Exposure to Mixed Phthalates in Czech Preschool and School Children - Puklová, Vladimíra; Janoš, Tomáš; Sochorová, Lenka; Vavrouš, Adam; Vrbík, Karel; Fialová, Alena; Hanzlíková, Lenka; Černá, Milena (Archives of environmental contamination and toxicology, 2019)
Knowledge of population exposure to phthalates based on the urinary metabolite levels is of the highest importance for health risk assessment. Such data are scarce in the Czech population. In the study conducted in 2016, six urinary phthalate metabolites were analysed in a total of 370 first morning urine samples of healthy children aged 5 and 9 years, namely mono(2-ethylhexyl) phthalate (MEHP), mono(2-ethyl-5-hydroxyhexyl) phthalate (5OH-MEHP), mono(2-ethyl-5-oxohexyl) phthalate (5oxo-MEHP), mono-benzyl phthalate (MBzP), mono-iso-butyl phthalate (MiBP), and mono-n-butyl phthalate (MnBP). The two latter mono-butyl phthalate isoforms dominated among all samples with geometric means of 63.0 µg/L (MnBP) and 44.1 µg/L (MiBP), followed by 5OH-MEHP (20.6 µg/L), 5oxo-MEHP (12.9 µg/L), MBzP (3.65 µg/L), and MEHP (2.31 µg/L). Daily intake (DI) of the parent phthalates was estimated using the creatinine-based model. The highest DI values were found for di-n-butyl phthalate (DnBP) (median 2.5 µg/kg bw/day; 95th percentile 7.8 µg/kg bw/day) and di-2-ethylhexyl phthalate (DEHP) (median 2.3 µg/kg bw/day; 95th percentile 8.9 µg/kg bw/day) in 5-year-old children. The tolerable daily intake (TDI) set by the European Food Safety Authority (EFSA) was exceeded in case of DnBP (in 1% of 9-year-olds and in 3% of 5-year-olds). Exposure risk was assessed based on hazard quotients calculation and cumulative approach for similar health effect. The combined exposure to four phthalates expressed by hazard index (HI) for reprotoxicity revealed exceeding of HI threshold in 14% of 5-year-olds and in 9% of 9-year-olds. These findings strongly support the need to reduce the burden of children by phthalates.
Keywords: Humans; dítě; kreatinin; Child; Schools; Female; Phthalic Acids; vystavení vlivu životního prostředí; lidé; Creatinine; látky znečišťující životní prostředí; No-Observed-Adverse-Effect Level; předškolní dítě; Environmental Pollutants; diethylhexylftalát; ženské pohlaví; Male; školy; dávka bez pozorovaného nepříznivého účinku; Czech Republic; Environmental Exposure; Diethylhexyl Phthalate; Risk Assessment; Česká republika; mužské pohlaví; Child, Preschool; kyseliny ftalové; hodnocení rizik